Evaluating of The Addition Coconut Pulp (Cocos Nucifera L) Fermentation in Feed and The Effect on Percentage of Carcass Broiler Chicken - Siti Rani Ayuti; M. Fikri; Rastina Rastina; Herrialfian Herrialfian; T. Zahrial Helmi; M. Isa; Rumi Sahara Zamzami (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
Broilers are chickens with high meat production. The productivity of broiler is seen from the percentage of carcass and abdominal fat. This study aims to determine the effect of giving fermented coconut pulp (Cocos nucifera L) on the percentage of carcass and abdominal fat of broilers. This study used a completely randomized design experimental method (CRD) consisting of 6 treatments and 6 replications so that the total observations were 36 units of observation. Each treatment had P1: 100% commercial feed without fermented coconut dregs, P2: 90% commercial feed + 10% fermented coconut dregs, P3: 80% commercial feed + 20% fermented coconut dregs, P4: 70% commercial feed + 30 % fermented coconut dregs, P5: 60% commercial feed + 40% fermented coconut dregs, P6 : 50% commercial feed + 50% fermented coconut dregs. The data were analyzed using the analysis of variance which was preceded by the battle test, followed by the Tukey test using the SPSS program. The analysis of variance showed significantly different results (P0.05) on the percentage of carcass and abdominal fat of the broiler. Tukey's follow-up test on the carcass showed a significant difference (P0.05) and there was no significant difference in fat (P0.05). It can be concluded that the supplementary feed of fermented coconut pulp can be used 40% as additional feed to increase the carcass percentage but not reduce the broiler abdominal fat percentage.